Human capital and ethnic self-identification of migrants - Laura Zimmermann; Liliya Gataullina; Amelie F. Constant; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2006)
The paper investigates the role of human capital for migrants' ethnic ties towards their home and host countries. Pre-migration characteristics dominate ethnic self-identification. Human capital acquired in the host country does not affect the attachment to the receiving country
Keywords: 330; Humankapital; Soziale Integration; Deutschland